Multiple Intracranial Tuberculomas: A Rare Case of CNS TB - Winarno, Agus Nur Salim (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Tuberculosis (TB) is still to be worlds major health concern. About 8,6 million cases occur in 2012 worldwide. TB doesnt mainly affect the lungs but it can affect extra pulmonary system. Central nervous system (CNS) is one complication of TB that should be considered as it is associated with high morbidity and mortality. Tuberculoma is one form of CNS TB that is rare and challenging in diagnostic. It will be presented a case of adult female with history of on-going TB treatment that presents with altered mental status, focal neurological signs, and increased ICP signs and symptoms. The head CT with contrast shows multiple ring enhancement with perilesional edema that consistent with brain tuberculoma. She was admitted to ICU and she got anti-TB drugs, and systemic steroid.